Government-incentivized crowdfunding for one-belt, one-road enterprises: design and research issues - Chang Heon Lee; J. Leon Zhao; Ghazwan Hassna (Financial Innovation, 2016)
Background: Local, state, and federal governments have started exploring the potential of crowdfunding in transforming conventional financing methods used previously to fund public projects and services. While crowdfunding has been applied to improve government financing methods in recent years, little is known about how this new model can be extended and applied in international collaboration among governmentincentivized projects. Methods: In this paper, we explores what roles crowdfunding can play as a financial intermediary to support government-incentivized multinational projects in the context of the One-Belt, One-Road initiative. Results: We conjecture that crowdfunding can offer an efficient mechanism to improve participatory budgeting and facilitate private-public collaboration while providing a high level of transparency in the budget decision process. Conclusions: The paper also discusses research issues and challenges, including features of the crowdfunding platforms that can affect the adoption and use of the crowdfunding platforms in multinational initiatives.
Keywords: 650; Crowdfunding; Government Incentivized Projects; Participatory Budgeting; Public-Private Collaboration; One Belt One Road